Clinical sub typing of newly detected type 2 diabetics on the basis of pancreatic beta cell function and degree of insulin resistance and their clinical characterization - Saha, Avijit (Asian Journal of Medical Sciences, 2022)
Background: Insulin resistance is a major cause for developing type 2 diabetes but is not synonymous with the type 2 diabetes. Pancreatic beta cell dysfunction probably needs to be sets in for clinical occurrence of type 2 diabetes. So knowledge regarding residual beta cell function and degree of insulin resistance is essential. Aims and Objectives: The objectives are as follows: (1) To estimate degree of insulin resistance (HOMA-IR) and pancreatic beta cell functional capacity (HOMA-B %) among newly detected Type 2 diabetics and (2) to identify different clinical phenotypic presentations of type 2 diabetes on the basis of these parameters. Materials and Methods: This present study was conducted in newly diagnosed type 2 diabeticpatients. After obtaining informed consent, anthropometric and clinical examination was carried out in all patients. Venous blood samples were drawn for fasting plasma glucose,c-peptide,fasting insulin level,HbA1c,lipid profile, etc.HOMA-IR and HOMA-B% were calculated with HOMA 2 calculator. Results: A total 100 newly diagnosed type 2 diabetic patients were studied. About 71% pt of study population had HOMA-B% value below 50% and half of study population had significant amount of insulin resistance. Three distinct clinical phenotypes had identified. Insulin resistance predominant group (30%), beta cell dysfunction predominant group (45%), and both abnormalities coexist group (25%). Conclusion: By the time of diagnosis of Type 2 diabetes, more than two-third study population had <50% residual beta cell function left and more than half had significant degree of insulin resistance. Hence,this functional assessment needs to be done for appropriate antidiabetic drug selection and for identification of different clinical phenotypes.